Investigation of shear and flexural failures of dapped-end connections with orthogonal reinforcement. (1st June 2022) - Rajapakse, Chathura; Degée, Hervé; Mihaylov, Boyan
Highlights: Reports experimental research of eight large-scale dapped-end connections. Detailed measurements of local and global deformations are provided. Observed behavior of the test specimens is discussed in detail. Effect of test variables on strength, crack control and rotation capacity are discussed. Flow of internal forces of test specimens are analyzed with FEM and kinematic models. Abstract: Reinforced concrete dapped-end connections are commonly used in precast structures due to ease of construction and the possibility to maintain a reduced structural depth. However, dapped-end connections typically feature inclined corner cracks at service loads due to stress concentrations at the re-entrant corner. Furthermore, these connections transfer high shear forces through a significantly reduced section. Due to these reasons, two main failure modes of dapped-end connections are identified as failures along a re-entrant corner crack and shear failures in the dapped-end region. This paper investigates such failure modes through an experimental campaign consisting of eight large-scale dapped-end tests. The main test variables are the amount of dapped-end reinforcement and the ratio of dapped-end horizontal to vertical reinforcement area. Detailed deformation measurements and an in-depth discussion on the behavior of the test specimens is presented. The effect of the test variables on the strength, crack control and rotation capacity of dapped-end connections is investigated. It was found that, for the same total area of horizontal and vertical reinforcement, connections featuring more horizontal reinforcement are stronger. While the orthogonal dapped-end reinforcement layout did not provide sufficient crack control under service loads, all connections exhibited substantial rotation capacity, including the shear critical connections. The flow of internal forces of the test specimens is further studied with a kinematics-based model and nonlinear finite element analysis.